2017
DOI: 10.1073/pnas.1703171114
|View full text |Cite
|
Sign up to set email alerts
|

Control of metastatic niche formation by targeting APBA3/Mint3 in inflammatory monocytes

Abstract: Cancer metastasis is intricately orchestrated by both cancer and normal cells, such as endothelial cells and macrophages. Monocytes/macrophages, which are often co-opted by cancer cells and promote tumor malignancy, acquire more than half of their energy from glycolysis even during normoxic conditions. This glycolytic activity is maintained during normoxia by the functions of hypoxia inducible factor 1 (HIF-1) and its activator APBA3. The mechanism by which APBA3 inhibition partially suppresses macrophage func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…On the one hand, there are data, in line with our work, showing that CCR2 + monocytes are cytotoxic (20) and antitumoral (37) and that CCL2 in breast cancer has an antimetastatic role (36,38,39). On the other hand, there are data showing that CCR2 + monocytes and CCL2 are involved in promoting metastatic breast cancer (40)(41)(42)(43)(44)(45). Notably, the great majority of prior studies showing that CCR2 + monocytes and CCL2 promote metastatic progression, have injected breast cancer cells i.v.…”
Section: Discussionsupporting
confidence: 84%
“…On the one hand, there are data, in line with our work, showing that CCR2 + monocytes are cytotoxic (20) and antitumoral (37) and that CCL2 in breast cancer has an antimetastatic role (36,38,39). On the other hand, there are data showing that CCR2 + monocytes and CCL2 are involved in promoting metastatic breast cancer (40)(41)(42)(43)(44)(45). Notably, the great majority of prior studies showing that CCR2 + monocytes and CCL2 promote metastatic progression, have injected breast cancer cells i.v.…”
Section: Discussionsupporting
confidence: 84%
“…It is necessary for metastasis to distant organs that the circulating tumour cells extravasate from the primary lesion, flow into the distant organ and then colonize it. Inflammatory monocytes of the organ enhance vascular permeability through vascular endothelial growth factor and induce the expression of E‐selectin (a cell adhesion molecule), leading to extravasation and colonization . We speculate that cigarette smoking could increase vascular permeability via inflammatory cytokines or physiological destruction due to fibrotic changes, which might promote influx of CRC cells into the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Munc18-1-interacting protein 3 (Mint3) can activate HIF-1 even under normoxic conditions by binding to and suppressing FIH-1 without affecting protein levels of HIF-1α [11]. Mint3 itself is expressed ubiquitously, but Mint3mediated HIF-1 activation is limited to some types of cells, such as cancer cells, macrophages, and cancer-associated fibroblasts, mainly due to the necessity of matrix metalloproteinase 14 expression, which supports stable interactions between Mint3 and FIH-1 in cells [7,[12][13][14][15][16]. Previously, we revealed that Mint3 depletion reduces HIF-1 activity during normoxia and tumorigenicity in breast cancer and fibrosarcoma [15,17].…”
Section: Introductionmentioning
confidence: 95%